Taxonomic study of the genus Spilonota Stephens (Lepidoptera: Tortricidae: Olethreutinae: Eucosmini) with descriptions of two new species in Korea - Choi, Seokhoon; Kim, Jeong-Nam; Bayarsaikhan, Ulziijargal; Jang, Chang Moon; Kim, Hanul; Nasu, Yoshitsugu; Bae, Yang-Seop (Zootaxa, 2024)
A taxonomic study of Spilonota Stephens, 1834, in Korea is conducted, and S. prognathana (Snellen, 1883) which had previously been merged with S. albicana (Motschulsky, 1866) is separated again. Additionally, as a result of research based on materials from Incheon National University two new species; S. samseong Choi, Bae & Nasu, S. laticucullusa Choi, Bae & Nasu proposed from Korea. The study provides brief descriptions of Spilonota species in Korea, with illustrations of the adult and genital morphology. Identification key for the known species reported from Korea is included.